MODERATION OF RELIGIOSITY IN THE RELATION OF INTERNET ADDICTION TO IMPULSE ONLINE BUYING (Study on State Islamic University of raden Intan Lampung Z Generation) - Al-Huda, Selfi; Kurnia, Redi A; Lia, Fitri (Sharia Business Management UIN Raden Intan Lampung, 2022)
Along with the spread of online shops in Indonesia and the variety of conveniences offered that will increase consumptive behavior of modern society, they not only buy things that they need but also buy things not important either. The research used quantitative method, namely research used to examine a particular population or sample, data analysis is quantitative or statistical, with the aim of testing the established hypothesis. The sampling method of the research used purposive sampling method. The population in this research were students of UIN Raden Intan Lampung who belonged to the Generation Z. Data collection techniques using questionnaires which is done by giving a set of questions or written statements to respondents and will answer by Google Form. The scale used is a Likert scale. The results of the data obtained from Generation Z students at UIN Raden Intan Lampung showed that the internet addiction variable has a positive and significant effect on impulse buying online, the first hypothesis is supported. The results of the moderation test of religiosity on the relationship between internet addiction and online impulse buying resulted in a negative original sample value and a significant p-value. It can be understood that religiosity weakens the relationship between internet addiction and online impulse buying.